Minimally invasive repair of iatrogenic right ventricular perforation guided by bedside contrast-enhanced ultrasound: A case report and literature review - Zhao, Yanchun; Lin, Yucheng; Hong, Zhiliang; Lai, Baochun; Lian, Lianghua; Chen, Lin; Xie, Qi; Zhou, Xiaofen; Wu, Songsong (Frontiers in Cardiovascular Medicine, 2022)
We report a 93-year-old woman with atrioventricular block who had right ventricular free wall perforation and rapid pericardial tamponade during installation of Micra Leadless Pacemaker. Pericardial catheter drainage was the primary emergency treatment. Considering the patient's physical condition and the special treatment conditions in the Intensive Care Unit, we tried a new emergency treatment method, that is, under intravenous anesthesia, a small intercostal incision in the bedside was performed to repair the right ventricular free wall perforation without cardiac arrest. It should be emphasized that ultrasound plays an important role in pinpoint the breach and intraoperative guidance. Contrast-enhanced ultrasound was first used to help locate the rupture, and bedside ultrasound guidance access to the rupture was performed with the minimum incision size (4cm). Our experience is expected to be popularized in the emergency treatment of right ventricular free wall perforation.